Melancolia e teoria da sedução generalizada : entre ligação e des-ligação - Lunardelli, Bruna Alvares (2012)
This is an essentially theoretical research in the context of psychoanalysis, whose main objective consisted in undertaking, from the standpoint of psychoanalytic theory - in particular, the Theory of Generalized Seduction, of Jean Laplanche - a reading frame of psychopathological melancholy. For this, resumed the thought found in psychoanalysis about the melancholy, being considered in this research, the work of Sigmund Freud, but only the texts that had close relationship with the subject studied. This review proposes to provide a basis for, from this, perform a laplanchean reading of this pathology. As a result, comes in the Theory of Generalized Seduction of Laplanche, which is characteristic displacement of the subject, and the notions of fundamental anthropological situation, cryptic message and original repression allowed melancholy place compared to other positions and questions. So we come up with the hypothesis that there is, in this pathology, a failure of secondary repression, that by not signing the original repression, it does give in and throws the psyche of the melancholy in a fight between the connection and disconnection drive, in which the superego has an important role, promoting an internal attack of otherness excessive that it conveys. Such an attack leads to a decrease instances ego its borders, leaving the individual in the area of sexuality off. The mobility of the boundaries of psychic instances in accordance with the greater or lesser disconnecting said drive therefore, in general, melancholic states, manic and free intervals observed in this pathology, as well as the switching characteristic between them.